EFEKTIVITAS PEMBELAJRAN BERBASIS PROYEK (PROJECT BASED LEARNING) TERHADAP HASIL BELAJAR MATA KULIAH EKONOMI KREATIF - Lubis, Putri Kemala Dewi; Revita Yuni; Khairani Alawiyah Matondang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The curriculum applied in the Bachelor of Economics Education study program at Medan State University uses the concept of Independent Learning with an output-oriented approach or Outcome-Based Education (OBE). In this output-based approach, results in the form of knowledge and skills must be measurable concretely. To achieve optimal measurement results, it is necessary to apply a project-based learning model that is in accordance with OBE principles in the study program. This OBE-based PJBL model is expected to be able to improve students' abilities as reflected in the achievement of their learning outcomes. This research uses research and development (R&D) methods, with a development model adapted from the ADDIE model. Based on the research results, 96.7% of students got an A grade, while 3.3% got an E grade. This shows that the PjBL model is very effective in improving student learning outcomes, especially in Creative Economy courses.